Nine Cautionary Tales. - Stauffer, B.
This paper describes nine hypothetical terrorist scenarios and describes the difficulty of carrying them out, the likelihood of them happening, and the potential damage to lives and property that they can do
Keywords: Attack damage; Attack prevention; Hypothetical terrorist scenarios